2007
DOI: 10.1590/s0004-27302007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Disfunção autonômica cardiovascular no diabetes mellitus experimental

Abstract: Much new information has been published in the last few years regarding pathophysiology of cardiovascular autonomic dysfunction in diabetic rats and mice. Our group has been studying the time-course cardiovascular changes associated with experimental diabetes in the last years, and obtained consistent evidences of severe dysautonomia in diabetes animal models. The aim of this manuscript is to review the contribution that studies involving different animal models of insulin deficiency or resistance have given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 85 publications
0
3
0
4
Order By: Relevance
“…20,23 Furthermore, the hyperglycaemia could have been responsible for the higher values found for LA in the saline and PD groups ( Table 2), as LA has been implicated as the main factor responsible for the chronicity of cutaneous lesions in diabetic humans and in rodents treated with STZ. 23,33,[35][36][37]…”
Section: Time (Days)mentioning
confidence: 99%
“…20,23 Furthermore, the hyperglycaemia could have been responsible for the higher values found for LA in the saline and PD groups ( Table 2), as LA has been implicated as the main factor responsible for the chronicity of cutaneous lesions in diabetic humans and in rodents treated with STZ. 23,33,[35][36][37]…”
Section: Time (Days)mentioning
confidence: 99%
“…Studies with experimental models have shown that the chemoreflex is decreased 29 . In humans, it has been observed a decrease in the peripheral chemoreflex in individuals with type 2 diabetes, especially regarding the response to hypoxia 30 .…”
Section: Chemoreflexes and Ventilatory Abnormalitiesmentioning
confidence: 99%
“…[ 10 – 12 ] Therefore, it is understood that studies on the behavior of blood pressure (BP), and heart rate (HR), as well as the autonomic control of circulation and glycemic control in diabetic individuals, may contribute to the understanding of the pathophysiological mechanisms involved. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%